Experimental Evaluation of Heat of Hydration in Concrete Incorporating Supplementary Cementitious Materials - Adveni Hesty Altisari Lada; Wahyuniarsih Sutrisno; Bambang Piscesa (Journal of Civil Engineering, 2024)
This research aims to study the impact of supplementary cementitious materials on the heatof hydration of concrete. The experimental tests were performed for concrete with threesize variations and seven variations of supplementary cementitious materials (SCMs) toinvestigate its impact on the heat of hydration. The SCMs used in this research mainlycome from industrial waste materials. Fly ash (FA), ground bottom ash (GBA), and silicafume (SF) were the waste materials used in this research. Tests were carried out for sevendays for each variation to observe the effect of volume changes and the addition of SCMson the change in concrete temperature. The experimental results indicated a directcorrelation between concrete volume and maximum temperature, with notable variationsin temperature distribution across the concrete mass. Typically, the highest temperaturewas observed at the core of the concrete. Fly ash (FA) and bottom ash (BA) demonstratedan inverse relationship between their content as supplementary cementitious materials(SCMs) and the maximum temperature achieved. Increasing the proportion of FA and BAin the concrete mixture resulted in a reduction of the hydration temperature. Additionally,silica fume (SF) was found to accelerate the hydration rate, though its efficacy in loweringthe heat of hydration was significant only when its content exceeded 5%.